Coagulopathy of Acute Sepsis - Semeraro, Nicola; Ammollo, Concetta T.; Semeraro, Fabrizio; Colucci, Mario (Seminars in Thrombosis and Hemostasis, 2015)
Coagulopathy is common in acute sepsis and may range from subclinical activation of blood coagulation (hypercoagulability), which may contribute to venous thromboembolism, to acute disseminated intravascular coagulation, characterized by widespread microvascular thrombosis and consumption of platelets and coagulation proteins, eventually causing bleeding. The key event underlying this life-threatening complication is the overwhelming inflammatory host response to the pathogen leading to the overexpression of inflammatory mediators. The latter, along with the microorganism and its derivatives drive the major changes responsible for massive thrombin formation and fibrin deposition: (1) aberrant expression of tissue factor mainly by monocytes-macrophages, (2) impairment of anticoagulant pathways, orchestrated by dysfunctional endothelial cells (ECs), and (3) suppression of fibrinolysis because of the overproduction of plasminogen activator inhibitor-1 by ECs and thrombin-mediated activation of thrombin-activatable fibrinolysis inhibitor. Neutrophils and other cells, upon activation or death, release nuclear materials (neutrophil extracellular traps and/or their components such as histones, DNA, lysosomal enzymes, and High Mobility Group Box-1), which have toxic, proinflammatory and prothrombotic properties thus contributing to clotting dysregulation. The ensuing microvascular thrombosis–ischemia significantly contributes to tissue injury and multiple organ dysfunction syndromes. These insights into the pathogenesis of sepsis-associated coagulopathy may have implications for the development of new diagnostic and therapeutic tools.
Keywords: infection; coagulation; fibrinolysis; neutrophil extracellular traps; microvascular thrombosis